2012
DOI: 10.1007/s12046-012-0097-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and microhardness of AA1050/TiC surface composite fabricated using friction stir processing

Abstract: Friction stir processing (FSP) has been developed by several researchers to produce an upper surface modification of metallic materials. The fabrication of TiC particulate (∼2 μm) reinforced aluminum matrix composite (AMC) using FSP is studied in this paper. The measured content of TiC powders were compacted into a groove of 0.5 mm × 5.5 mm. A single pass FSP was carried out using a tool rotational speed of 1600 rpm, processing speed of 60 mm/min and axial force of 10 kN. A tool made of HCHCr steel, oil harden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The hardness value of the SZ increased by 58 % when compared to the base metal for sample C1. Thangarasu 21 suggested four methods of hardening in FSW MMC:…”
Section: Microhardness Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…The hardness value of the SZ increased by 58 % when compared to the base metal for sample C1. Thangarasu 21 suggested four methods of hardening in FSW MMC:…”
Section: Microhardness Profilingmentioning
confidence: 99%
“…[19][20][21][22] These studies concluded that grain refinement was achieved using the FSP process. An improved particle distribution and better mechanical properties were also observed.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion properties of aluminum sheets reinforced with alumina, corroded in tetraoxosulphate (iv) acid as corrosion medium, revealed better corrosion properties compared to unreinforced samples [7]. Titanium carbide particulate addition in the weld seam of aluminum 1050 substrate by friction stir welding process, also revealed better mechanical properties [8]. The wear resistance property and the hardness values of aluminum-titanium-carbide composite were higher than those of the base material [9].…”
Section: Introductionmentioning
confidence: 97%
“…9 These composites can suffer a great loss in ductility and toughness due to the incorporation of non-deformable ceramic reinforcements, which limits their wide applications to a certain extent. 10,11 However, the nature of the technique used to fabricate particle-reinforced metal-matrix composites (MMCs) has been shown to have a significant effect on the product's mechanical properties and hence the applications for which it is suitable. [12][13][14][15] Surfacemodification techniques such as high-energy laser beam, plasma spraying, cast sinter and electron beam irradiation have been developed over the past two decades to fabricate Surface Metal Matrix Composites (SMMCs).…”
Section: Introductionmentioning
confidence: 99%
“…A significant improvement in the wear resistance of the nano-composite layer was observed as compared to that of the as-received substrate and the enhanced properties are attributed to the uniform dispersion of hard nano-sized TiC reinforcements in a matrix of ultra-fine dynamically recrystallized grains. A. Thangarasu et al 10 fabricated TiC particulates (»2 μm) and reinforced them with an aluminium matrix composite (AMC) using FSP. The powders were compacted into a groove and a single pass FSP was carried out using a tool rotational speed of 1600 min -1 and a processing speed of 60 mm/min.…”
Section: Introductionmentioning
confidence: 99%